PELATIHAN TECHNOPRENEURSHIP PEMBUATAN MEDIA EDUKATIF RAMAH LINGKUNGAN BERBASIS GREEN ECONOMY PADA SISWA SMP 2 KERINCI - Sahara Sahara; Iwan Putra; Nurmala Sari; Novia Sri Dwijayanti; Dwi Rayana Siregar (Jurnal Pengabdian Masyarakat Khatulistiwa, 2025)
ABSTRACTThe training and technical assistance activities on technopreneurship for the creation of eco-friendly educational media based on the green economy were carried out with students of SMP Negeri 2 Kerinci as an effort to foster creativity, innovation, and entrepreneurial spirit from an early age. This program was designed to integrate the concept of environmental sustainability with the development of entrepreneurial skills (edupreneurship), enabling students not only to produce educational media that are useful for the learning process but also to have economic value. The methods applied included the dissemination of green economy concepts, practical training in creating educational media from recycled materials, and technical assistance throughout the production process to simple marketing. The results of the activities indicated an increase in students’ understanding of the importance of environmental friendliness in entrepreneurship, improvement of skills in creating creative products, and the growth of motivation to develop business ideas based on education and the environment. Therefore, this program is expected to serve as an initial step in building a culture of edupreneurship among students, in line with the principles of sustainable development.Keywords: Technopreneurship, green economy, educational media, edupreneurship, students ABSTRAKKegiatan pelatihan dan pendampingan teknis technopreneurship pembuatan media edukatif ramah lingkungan berbasis green economy dilaksanakan pada siswa SMP Negeri 2 Kerinci sebagai upaya menumbuhkan jiwa kreatif, inovatif, dan berwirausaha sejak dini. Program ini dirancang untuk mengintegrasikan konsep keberlanjutan lingkungan dengan pengembangan keterampilan kewirausahaan (edupreneurship), sehingga siswa tidak hanya mampu menghasilkan produk media edukatif yang bermanfaat dalam proses pembelajaran, tetapi juga memiliki nilai ekonomis. Metode yang digunakan meliputi sosialisasi konsep green economy, pelatihan keterampilan praktis pembuatan media edukatif dari bahan daur ulang, serta pendampingan teknis dalam proses produksi hingga pemasaran sederhana. Hasil kegiatan menunjukkan peningkatan pemahaman siswa mengenai pentingnya ramah lingkungan dalam wirausaha, keterampilan dalam menciptakan produk kreatif, serta tumbuhnya motivasi untuk mengembangkan ide-ide usaha berbasis pendidikan dan lingkungan. Dengan demikian, kegiatan ini diharapkan dapat menjadi langkah awal dalam membangun budaya edupreneurship di kalangan pelajar, yang selaras dengan prinsip pembangunan berkelanjutan.Kata Kunci: technopreneurship, green economy, media edukatif, edupreneurship, siswa